Fourier Coefficients of a Class of Eta Quotients of Weight 4 - Kendirli, Barış (International Journal of Advanced Mathematical Sciences, 2016)
Recently, there have been several works on the coefficients of the Fourier series expansions of a class of eta quotients by Williams, Yao, Xia and Jin, Kendirli, and Alaca. Some important explicit formulas have been discovered. Williams expressed all coefficients of one hundred and twenty-six eta quotients in terms of  and  and Yao, Xia and Jin, following the method of proof of Williams, expressed only even coefficients of one hundred and four eta quotients in terms of  and  The author has expressed the even and odd coefficients of the Fourier series expansions of a class of eta quotients in terms of  and  for  Meanwhile, Alaca has obtained the coefficients of the Fourier series expansions of a class of eta quotients in  in terms of  and  Here, we will express the coefficients of the Fourier series expansions of a class of eta quotients in  in terms of  and Fourier coefficients of the four eta quotients.